Re-Konstruktionen - Krisenthematisierungen in der Erwachsenenbildung - Ebner von Eschenbach, Malte; Käpplinger, Bernd; Kondratjuk, Maria; Kraus, Katrin; Rohs, Matthias; Niemeyer, Beatrix (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2023)
The Corona crisis is the occasion for the thematisation of crises in the context of adult/continuing education. The title "Re-Constructions" aims to make other crisis phenomena - ecological, economic, social, psychological, political or biographical - that are significant in the context of adult/continuing education the object of reflection. The pandemic is thus the exemplary starting point, because it has affected adult education in many ways. Adult education can provide a space for reflection in which a critical examination of the social implications of this and other exceptional experiences in society as a whole can take place and collective educational processes can become possible.